2016
DOI: 10.1152/ajpregu.00453.2015
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide and fever: immune-to-brain signaling vs. thermogenesis in chicks

Abstract: Nitric oxide (NO) plays a role in thermogenesis but does not mediate immune-to-brain febrigenic signaling in rats. There are suggestions of a different situation in birds, but the underlying evidence is not compelling. The present study was designed to clarify this matter in 5-day-old chicks challenged with a low or high dose of bacterial LPS. The lower LPS dose (2 μg/kg im) induced fever at 3-5 h postinjection, whereas 100 μg/kg im decreased core body temperature (Tc) (at 1 h) followed by fever (at 4 or 5 h).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 73 publications
(106 reference statements)
0
26
0
7
Order By: Relevance
“…The first group was placed in an independent temperature-controlled room at 23 ± 2 • C. The broiler chicks from the second group were placed in a heat-stressed room and exposed to chronic heat stress conditions (32 ± 2 • C) for seven hours per day from 8:00 a.m. to 3:00 p.m. The indoor relative humidity and temperature under thermoneutral conditions during the experimental period for the broiler was 51.2% and 23.1 • C, 57% and 23.9 • C, and 53% and 24.7 • C during days [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], and 34-41 of age, respectively. Under chronic heat stress conditions, the indoor relative humidity and temperature was 44.9% and 31.5 • C, 47.8% and 31.8 • C, and 41.8% and 31.9 • C during days [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], and 34-41 of age, respectively.…”
mentioning
confidence: 99%
“…The first group was placed in an independent temperature-controlled room at 23 ± 2 • C. The broiler chicks from the second group were placed in a heat-stressed room and exposed to chronic heat stress conditions (32 ± 2 • C) for seven hours per day from 8:00 a.m. to 3:00 p.m. The indoor relative humidity and temperature under thermoneutral conditions during the experimental period for the broiler was 51.2% and 23.1 • C, 57% and 23.9 • C, and 53% and 24.7 • C during days [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], and 34-41 of age, respectively. Under chronic heat stress conditions, the indoor relative humidity and temperature was 44.9% and 31.5 • C, 47.8% and 31.8 • C, and 41.8% and 31.9 • C during days [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], and 34-41 of age, respectively.…”
mentioning
confidence: 99%
“…These lines of evidence raise the question as to whether heightened H + production in endotoxic shock could result from metabolic alterations unrelated to anaerobic metabolism. From this perspective, it is relevant to point out that whole-body oxygen consumption ( _ VO 2 ) is known to fall in conjunction with core temperature (T c ) early in the course of endotoxic shock in unanesthetized rats (Derijk et al 1994;Romanovsky et al 1996;Garrett-Cox et al 2003) as well as in chicks (Dantonio et al 2016). Recently, Corrigan et al (2014) have shown that, at least in rats, this hypometabolic, hypothermic response occurs when neither oxygen delivery nor mitochondrial function is impaired to the point of compromising aerobic metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Portanto, a febre é definida comparando essas temperaturas preferidas em estado de infecção com aquelas em condições de normotermia Boltaña et al, 2013). Neste contexto, normotermia poderia ser definida como o estado no qual a temperatura central e o set point são a mesma, mas sem aumento prolongado da temperatura preferencial e corporal (Kluger, 1991; (Stitt, 1973;Lipton & Fossler, 1974;D'Alecy & Kluger, 1975;Blatteis, 1976;Van Miert et al, 1977;Berendt et al, 1980;Van Miert et al, 1986;Kluger, 1991;Gregorut et al, 1992;Van Miert et al, 1992;Johnson et al, 1993;Roth et al, 1994;Sehic et al, 1996;Maloney & Gray, 1998;Koutsos & Klasing 2001;Rudaya et al, 2005;Mahmoud et al, 2007;De Boever et al, 2010;Nakamura & Morrison, 2011;Sköld et al, 2015;Dantonio et al, 2016). Répteis, peixes,…”
Section: O Que é Febre Comportamental?unclassified